Non-state ordering in the post-apartheid South Africa - a study of some structures of non-state ordering in the western cape province - Tshehla, Boyane John (Department of Private Law, 2026)
Social ordering is an integral part of human life - it is the heart of society and, extending the metaphor, health of society depends on its consistent and regular activity. Throughout history nations and communities invented (and reinvented) ways of ordering their lives. There is no record of any form of community or society that existed without agreed ground rules as to how individuals and groups ought to behave and ways to enforce adherence to such ground rules. According to Thomas Hobbes' such ground rules constitute a social contract. He observed that people come together to give away some of their rights, especially the use of force, for the good of all. Without social contract, the great man reasoned, life would be "solitary, poor, nasty, brutish, and short" (Nina 200 I: 10 l) owing to the selfish nature of human beings. Michel Foucault, the famous French Philosopher, sees these ground rules of living together as 'conduct of conduct'.